2013
DOI: 10.1002/bdrc.21039
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in heart regeneration

Abstract: Although cardiac stem cells (CSCs) and tissue engineering are very promising for cardiac regenerative medicine, studies with model organisms for heart regeneration will provide alternative therapeutic targets and opportunities. Here, we present a review on heart regeneration, with a particular focus on the most recent work in mouse and zebrafish. We attempt to summarize the recent progresses and bottlenecks of CSCs and tissue engineering for heart regeneration; and emphasize what we have learned from mouse and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 120 publications
0
13
0
Order By: Relevance
“…Many efforts are devoted to cardiac stem cell generation and tissue engineering, although making cardiac stem cells or tissue scaffolds functionally integrated into their host cardiac tissues remains difficult in clinical settings [1,2]. A number of studies have shown that the adult mammalian heart has limited regenerative capacity, although not sufficient to fully restore heart function after substantial myocardial injury [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many efforts are devoted to cardiac stem cell generation and tissue engineering, although making cardiac stem cells or tissue scaffolds functionally integrated into their host cardiac tissues remains difficult in clinical settings [1,2]. A number of studies have shown that the adult mammalian heart has limited regenerative capacity, although not sufficient to fully restore heart function after substantial myocardial injury [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts are devoted to cardiac stem cell generation and tissue engineering, although making cardiac stem cells or tissue scaffolds functionally integrated into their host cardiac tissues remains difficult in clinical settings [1,2]. A number of studies have shown that the adult mammalian heart has limited regenerative capacity, although not sufficient to fully restore heart function after substantial myocardial injury [2]. On the other hand, the adult zebrafish and newt hearts have full capacity of cardiac regeneration after ventricular resection or cryoinjury, making zebrafish and newt as powerful animal models for studying heart regeneration in particular and organ regeneration in general [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Stem cells also help in dental cares by inducing regeneration or differentiation of dental epithelia into enamel-producing ameloblasts [86]. MSCs implanted in pancreas can replace defective islet beta cells, enhance β-cell proliferation [87], cure type 1 diabetes [88] and do its reversal [89,90,98,99] in non-obese diabetic mice [91,92]. Similarly, implantation of multipotent stem cells implanted in bone marrow can suppress ovarian cancer and stop metastasis [90,92].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Similarly, implantation of multipotent stem cells implanted in bone marrow can suppress ovarian cancer and stop metastasis [90,92]. These are also implanted to remove incurable defects like tumors by counterbalance between mature BDNF and proBDNF factors that may regulate tumor growth [88,93]. HSCs stem cell transplantation is used in [94,96].…”
Section: Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation